2023
DOI: 10.1038/s41560-023-01249-0
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional hole-shuttle molecule for improved interfacial energy level alignment and defect passivation in perovskite solar cells

Abstract: Perovskite solar cells have reached a power conversion efficiency over 25%, and the engineering of the interface between the perovskite and hole transport layer (HTL) has been crucial to achieve high performance. Here we design a bifunctional molecule CBz-PAI with carbazole-triphenylamine and phenylammonium iodide units to passivate defects at the perovskite/HTL interface. Owing to a favourable energy level alignment with the perovskite, the CBz-PAI acts as a hole shuttle between the perovskite layer and the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 49 publications
2
51
0
Order By: Relevance
“…PLQY results showed that SC could significantly inhibit the nonradiative recombination in Pb-Sn perovskite, mainly because SC regulated the morphology of perovskite films and passivated surface defects. [52,53] In addition, time-resolved photoluminescence (TRPL) decay measurements were performed to compare dynamic characteristics of photogenerated carriers for control and SC films. As shown in Figure 4e and Table S2 (Supporting Information), compared with control film (120.9 ns), SC film (282.1 ns) had a longer average lifetime (𝜏 avg ).…”
Section: Resultsmentioning
confidence: 99%
“…PLQY results showed that SC could significantly inhibit the nonradiative recombination in Pb-Sn perovskite, mainly because SC regulated the morphology of perovskite films and passivated surface defects. [52,53] In addition, time-resolved photoluminescence (TRPL) decay measurements were performed to compare dynamic characteristics of photogenerated carriers for control and SC films. As shown in Figure 4e and Table S2 (Supporting Information), compared with control film (120.9 ns), SC film (282.1 ns) had a longer average lifetime (𝜏 avg ).…”
Section: Resultsmentioning
confidence: 99%
“…The built-in potential (V bi ) from the Mott-Schottky (M-S) plots is extended from 1.0 to 1.03 V by CsCl:Eu 3+ modification (Figure S18, Supporting Information), confirming less V oc loss from interfacial recombination in CsCl:Eu 3+ PSCs. [36] The V oc performance correspondingly increases as the bandgap expands. [37] It is more reasonable to compare the V oc deficit of the CsCl-and CsCl:Eu 3+ -modified PSCs owing to the E g difference (1.537 and 1.507 eV) (Figure 4f).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, developing suitable interfacial materials is beneficial to improve both V OC and FF, and thus effectively improve PCE. [ 1,164,165 ]…”
Section: Implementation Of ML For the Advancement Of Efficient And St...mentioning
confidence: 99%